Melody transcatheter pulmonary valve implantation. Results from the registry of the Italian society of pediatric cardiology - Butera, Gianfranco; Milanesi, Ornella; Spadoni, Isabella; Piazza, Luciane; Donti, Andrea; Ricci, Christian; Agnoletti, Gabriella; Pangrazi, Alberta; Chessa, Massimo; Carminati, Mario (Catheterization and cardiovascular interventions, 2013)
Background and aims Percutaneous implantation of pulmonary valve has been recently introduced in the clinical practice. Our aim was to analyze data of patients treated in Italy by using the Melody Medtronic valve. Methods Prospective, observational, multi‐centric survey by means of a web‐based database registry of the Italian Society of Pediatric Cardiology (SICP). Results Between October 2007 and October 2010, 63 patients were included in the registry (median age: 24 years; range 11–65 years). Forty subjects were in NYHA class I–II while 23 were in NYHA class III–IV. Patients included had a history of a median three previous surgeries (range 1–5) and a median of one previous cardiac catheterization (range 0–4). A cono‐truncal disease was present in 39 patients, previous Ross operation in 9, and other diagnosis in 15. Indication to valve implantation was pure stenosis in 21 patients, pure regurgitation in 12, association of stenosis and regurgitation in 30. Implantation was performed in 61 subjects (97%). Pre‐stenting was performed in 85% of cases. Median procedure time was 170 minutes (range 85–360). No significant regurgitation was recorded after procedure while the trans‐pulmonary gradient reduced significantly. Early major complications occurred in seven subjects (11%). One death occurred in the early post‐operative period in a severely ill subject. At a median follow‐up of 30 months (range 12–48 months), three patients died due to underlying disease. Major complications occurred in six patients during follow‐up (external electric cardioversion: one patient; herpes virus encephalitis: two patients; Melody valve endocarditis needing surgical explant: two patients; major fractures of the stent and need second Melody valve implantation: two patients). Freedom from valve failure at latest follow‐up was 81.4% ± 9%. Conclusion Early results of the SICP registry on transcatheter Melody pulmonary valve implantation show that the procedure is safe and successful. Major concerns are related to the occurrence of stent fracture and bacterial endocarditis. Longer follow‐up and larger series are needed. © 2012 Wiley Periodicals, Inc.